2019
DOI: 10.1002/term.2924
|View full text |Cite
|
Sign up to set email alerts
|

Kidney‐in‐a‐lymph node: A novel organogenesis assay to model human renal development and test nephron progenitor cell fates

Abstract: Stem cell‐derived organoids are emerging as sophisticated models for studying development and disease and as potential sources for developing organ substitutes. Unfortunately, although organoids containing renal structures have been generated from mouse and human pluripotent stem cells, there are still critical unanswered questions that are difficult to attain via in vitro systems, including whether these nonvascularized organoids have a stable and physiologically relevant phenotype or whether a suitable trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…LNs and omenta can be used as bioreactors to grow organs. LN grafting is a unique approach pioneered by our laboratory, 11,12,24,34,35 with no previous records in the literature. Conversely, the greater omentum has long been described as an ideal transplantation site mainly for its easy accessibility and large vascular network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LNs and omenta can be used as bioreactors to grow organs. LN grafting is a unique approach pioneered by our laboratory, 11,12,24,34,35 with no previous records in the literature. Conversely, the greater omentum has long been described as an ideal transplantation site mainly for its easy accessibility and large vascular network.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Even more impressive were the data of human fetal kidney engraftment inside the LN, which clearly indicated that, although the donor and host endothelial cells could coexist in the early stages of engraftment, over time the grafts were entirely re-vascularized by host cells. 24 Figure 1A shows abundance of host (GFP À ) endothelial cells (CD31 þ ) in the interstitium of a GFP þ mouse metanephric kidney 3 weeks after transplantation in the LN, as well as the presence of a host endothelial cell in an engrafted glomerulus. Most glomerular endothelial cells (CD34 þ ) expressed NIK (Figure 1B).…”
Section: Vascularization Of Glomeruli Engrafted In the Mouse Ln Might Be Driven By Host Ltbr/nik Axismentioning
confidence: 99%
“…Lymph nodes are a highly favorable site for ectopic cell transplantation. 19 , 29 , 30 , 31 Not only do their plasticity and highly complex vascular network provide a healthy milieu for cell engraftment and expansion, but their accessibility makes it possible to perform minimally invasive cell delivery in the clinical setting. Ultrasound-guided lymph node identification and targeting are commonly performed clinically, and multiple clinical studies have employed lymph nodes as sites for injection of immunotherapeutic agents, with patients rating the procedure comparable to a subcutaneous injection and less painful than venipuncture.…”
Section: Discussionmentioning
confidence: 99%
“…Cultured fetal kidneys 8 or organoids made from embryonic kidney cells 9 also become vascularized and form mature and functional glomeruli following in vivo transplantation. More recent studies have shown that mouse 10 and human 11 kidney primordia transplanted into the lymph node (LN) can also grow and mature into functional miniorgans.…”
Section: Growing Embryonic Kidneys In Living Animalsmentioning
confidence: 99%
“…Earlier studies by Francipane showed that embryonic kidneys transplanted into mouse LNs develop mature nephrons with a vascular network that originates from both host and graft-derived vascular cells. 10,11,14 Although these studies demonstrated that the LN provides an appropriate niche for transplanting and growing embryonic kidneys, the cellular and molecular mechanisms that govern organogenesis within the LN remain unknown.…”
Section: Vascularization Of Glomeruli Engrafted Into Mouse Ln Might Bmentioning
confidence: 99%